Forensic evaluations of drug endangered children: "My house caught on fire; my cat jumped out the window". (August 2016) - Shukla, Rashi K.; Bell, Kathy; Maier, Elizabeth A.; Newton, David C.
Abstract: Although there is a sizeable body of empirical literature examining the health consequences of exposure to drug use and manufacture in childhood, little is known about how drug endangered children themselves perceive their environment and situation. This study examines the types of information obtained from forensic medical evaluations that include the collection of verbal accounts from children about their situations. Forensic medical examination reports of 173 children removed from residences where methamphetamine manufacturing was suspected of occurring were analyzed. The children's verbal accounts highlight themes of hazards and toxins in the home, criminal and delinquent activity among children and caregivers, knowledge of drug-related activity, poor health and well-being, and traumatic law enforcement encounters. Drug endangered children represent a shadow population often overlooked in responses to the drug problem. Drug-related research and responses should prioritize children and their long-term well-being. Further research on the short- and long-term impacts of exposure as well as the social and physical development of these children is needed. Highlights: Drug endangered children can be viewed as a shadow population who are often overlooked in responses to the drug problem. Drug-related research and responses should prioritize children and their well-being. Drug endangered children are able to provide insight into the home environments and situations to which they were exposed. Children's verbal accounts serve as a valuable source of information for medical professionals and child protective services.